Phytochemicals screening and total phenolic content of Malaysian Zea mays hair extracts - Solihah, M.A.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
In the present study, Malaysian Zea mays hair extracts are screened for the occurrence of bioactive compounds. The results positively showed the present of flavonoids, saponin, tannins, phlobatannins, phenols, alkaloids and cardiac glycosides in both aqueous and methanolic extract of Zea mays hair. Terpenoid compounds however present only in the methanolic extract sample. In addition, the total phenolic content (TPC) in aqueous extract was significantly higher (42.71 + 0.87 μg/g of tannic acid equivalent (TAE)) compared to methanolic extract (40.38 + 1.10 μg/g of TAE). The findings suggested that phytochemicals present in Zea mays hair are potentially beneficial as therapeutic and antioxidative agents in pharmaceuticals, food and other related industries.